Brain Cholinergic Mechanisms - Sukumar Vijayaraghavan (Frontiers Research Topics, 2016)
Much of our understanding of brain physiology has focused on what one might call, first order processes. These essentially include the primary synaptic mechanisms underlying excitation (mainly glutamate) and inhibition (mainly GABA). Our attention has focused on how the balance of excitation and inhibition regulates the timing, patterns, and extent of information flow across various circuits. A lot less is understood regarding second order processes that sculpt and modify these primary interactions. One such modulatory transmitter in the brain is acetylcholine (ACh). The importance of ACh in modulating various behaviors related to learning, memory, and attention has been recognized over the last four decades as has its involvement in various neurodegenerative and psychiatric disorders. However, our understanding of the mechanistic bases for these actions is at its infancy, at best and much remains to be understood. The array of receptor subtypes for nicotinic and muscarinic receptors, their different locations, and complex signal transduction mechanisms remain a puzzle. Transmitter (ACh) release sites and their relationship to receptor loci are poorly understood. Overall, we lack a unifying framework for conceptualizing how disparate actions of the transmitter on receptors lead to circuit modulation and, eventually, influences on cognition. By its very nature, reports on cholinergic signaling are quite scattered, presented in journals across sub-disciplines and in the context of the systems they modulate. Hence, there is need for consolidation of these studies under a single cover that would allow one to compare and contrast the effects of this transmitter across systems and contexts. This special issue represents one such compilation. The issue addresses cholinergic modulation of defined circuits that lead to specific behaviors and consists of a judicious mixture of review articles and primary papers. The articles focus on three aspects of the system: 1) Cellular targets of cholinergic signaling. 2) Receptor mechanisms. 3) Endogenous transmitter distribution and action. While no common mechanism emerges that can explain cholinergic actions on brain functions, on can postulate that the transmitter system is dynamic, modulating the balance of excitation and inhibition in various circuits. This modulation sets up timed network oscillations and it is tempting to speculate that these oscillations form a template for better encoding of afferent inputs. One can broadly envision the role of the cholinergic system as facilitating processes that allow for more efficient acquisition of learning and engraving of memories. Thus, understanding the mechanisms underlying tonic and stimulus-dependent release of ACh and how it alters firing templates of neuronal networks would be the first step towards elucidating its role in learning and memory. This special topics edition provides clues to some of the actions of ACh. It is hoped that the articles allow the reader to extract common themes and potential mechanisms of cholinergic regulation that will lead to elucidation of general principles governing the actions of this important neuromodulator.